Seroprevalence of Toxoplasma gondii IgG antibody in HIV/AIDS-infected individuals in Maputo, Mozambique - Abílio Domingos; Lucy Sayuri Ito; Elizabeth Coelho; Jorge Manuel Lúcio; Luiza Harunari Matida; Alberto Novaes Ramos Jr (Universidade de São Paulo, 2013)
OBJECTIVE To analyze the prevalence of IgG antibodies to Toxoplasma gondii in patients infected with HIV/AIDS and the association of demographic and social variables. METHODS Descriptive cross-sectional study that included the analysis of sociodemographic data and laboratory findings of 200 patients infected with HIV/AIDS treated in a laboratory unit in Maputo, Mozambique, in 2010. Individual data for all participants were collected with a self-administered questionnaire. Plasma samples were tested for IgG testing of anti- T. gondii using hemagglutination for the analysis of antibodies. RESULTS The seroprevalence of IgG anti- T. gondii was 46.0% (95%CI 39.2;52.9), 39.3% (95%CI 29.5;50.0) in men and 50.9% (95%CI 41.9;59.8) in women, with no difference between sex (OR 1.30; 95%CI 0.95;1.77; p = 0.12). Ages ranged from 10 to 60 years, with a higher prevalence of infection in older age groups, but with no significant difference between them. Regularly consuming cattle meat (OR 1.74; 95%CI 1.04;2.89, p = 0.05), breeding cats/dogs (OR 6.18; 95%CI 3.60;10.62, p < 0.000) and having regular contact with soil (OR 3.38; 95%CI 2.19;5.21; p < 0.000) were significantly associated with risk of latent infection. CONCLUSIONS Toxoplasmosis is an infection with high prevalence in Mozambique. Cultural and behavioral aspects increase the risk. Toxoplasmosis can be responsible in our environment by the great burden of morbidity and mortality associated with meningoencephalic injuries in patients with HIV/AIDS.